Análisis de la estructura del guion del corto documental ecuatoriano Rosita de Ileana Matamoros - Aguilar Vargas, Daniel Enrique (2020)
The story through audiovisual media is more than writing, it is also the entire commitment of a production team. The purpose of this paper is to analyze the structure of the short film “Rosita”, guided and directed by Ileana Matamoros in 2018. It is a qualitative investigation in which techniques such as observation and interview are used, in which are studied the different elements of a documentary. For this, a case study is realized, which is the direct observation of the film "Rosita"; and 11 questions are also asked in an unstructured individual interview. The results evidences that the structure of a documentary is important when writing a script, because this will allow the development of the film. Concluding that, a documentary tell people about the story of a subject, which can be interpreted from different points of view, and also, all the elements of the script are the fundamental basis for its realization. Thus, it is recommended an extensive time for its realization and the intrinsic study of the characters.